115 The Southwestern Aneurysm Scoring Index Prediction of Outcomes at 1 Year in Ruptured Aneurysms Treated With Microsurgery. (1st August 2016) - Ban, Vin Shen; Beecher, Jeffrey S.; Eddleman, Christopher S.; Aoun, Salah G.; Lyon, Kristopher Allen; El Ahmadieh, Tarek Youssef; McDougall, Cameron Michael; Welch, Babu Guai; Reisch, Joan; Batjer, H. Hunt; Samson, Duke S.; White, Jonathan A.
Abstract: INTRODUCTION: Predicting outcome after aneurysmal rupture can be challenging. The Southwestern Aneurysm Severity Index (SASI) was developed to aid aneurysm treatment outcome prediction. In this introduction of SASI, we analyzed patients with ruptured aneurysms treated microsurgically. With the use of this cohort, each SASI element was evaluated to measure its value to the overall index. METHODS: Patients presenting to our institution with ruptured aneurysms from 2000 to 2014 treated with microsurgery were included. Outcome was defined as Glasgow Outcome Scale (GOS) at 1 year (GOS12m) dichotomized to 1 to 3 vs 4 to 5. The SASI was composed of multiple prospectively recorded patient demographic, clinical, radiographic, and aneurysm-specific variables. Univariate and multivariate analyses were used to construct the best predictive models for patient outcome. RESULTS: We identified 527 eligible patients. The median age was 53 years (interquartile range: 19) and 72% were female. The GOS12m was 1 to 3 in 152 patients (28.8%) and 4 to 5 in 375 patients (71.2%). In the univariate χ 2 analysis, Hunt-Hess ( P < .001), Nonneurological ASA (NNASA, P < .001), normal CT ( P < .014), subarachnoid hemorrhage ( P < .001), intracerebral hemorrhage (ICH) ( P < .001), intraventricular hemorrhage (IVH) ( P < .001), hydrocephalus ( P < .001), aneurysm location ( P = .021), calcification/thrombosis ( P = .004), age >64 ( P < .001), and size >20 mm ( P < .001) were significant predictors of GOS12m. In the multivariate stepwise logistic regression, the best predictive model for poor outcome (without Hunt-Hess and/or NNASA) included ICH (odds ratio [OR], 2.19; 95% confidence interval [CI], 1.54-3.10), IVH (OR, 1.99; 95% CI, 1.17-3.39), hydrocephalus (OR, 1.99; 95% CI, 1.17-3.38), location (OR, 1.84; 95% CI, 1.30-2.60), age >64 (OR, 5.09; 95% CI, 3.12-8.30), and size >20 mm (OR, 5.21; 95% CI, 2.35-11.57). A scoring system was created utilizing the β-coefficients from the logistic regression. This scoring system predicts GOS12m with good accuracy (receiver operating characteristic-area under the curve, 0.813; 95% CI, 0.773-0.853). CONCLUSION: Several elements were identified as being predictive of GOS12m after microsurgery for ruptured aneurysms. SASI was a stronger predictor than each of these individual factors alone and provides an accurate prediction of GOS12m at presentation, thus improving patient or family expectations and possibly guiding therapeutic efforts.